INDICATORS OF MANIFESTATIONS OF DEVIANT BEHAVIOR OF YOUNG ATHLETES IN THE PROCESS OF TRAINING ACTIVITY - Skok, N.S.; Makarov, Yu.M.; Kulikov, V.S.; Lutkova, N.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the causes and types of manifestations of deviant behavior of young athletes in the process of training activities based on the results of an expert survey. Methods and structure of the study. In the course of the research work "Development of evidence-based proposals for the prevention, correction of deviant behavior and the formation of value orientations among athletes from among the sports reserve", an expert survey was conducted (January-February 2022) (n=20), the information received was processed with using SPSS 23.0. Results and conclusions. An analysis of the results of the expert survey made it possible to identify the most significant causes that contribute to the emergence of manifestations of deviant behavior in young athletes: the influence of peers; environment outside the sports environment; lack of understanding and positive experience of interaction in the family (with relatives); indifference of coaches and other sports professionals (ignoring the personal problems of young athletes); increased level of anxiety. The types of manifestations of deviant behavior, predisposition to which can be observed in young athletes, are revealed: addictive, affective, aggressive.